Assessment of Different Orange Juices and Beverages on Blood Antioxidant Capacity of Healthy Individuals - Ferreira, Paula S. [UNESP]; Goncalves, Danielle R. [UNESP]; Nery, Marina S. [UNESP]; Zang, Kathy; Cesar, Thais B. [UNESP]; Baldwin, Elizabeth A.; Fla State Hort Soc (Florida State Horticultural Soc, 2017)
Orange juice and orange sugary beverages contain varying amounts of nutrients known to contribute to human health, as well as citrus bioactive compounds. However, the benefit of different types of citrus beverages and their contribution to blood antioxidant activity are not completely known. To explore the benefits of the bioactive ingredients present in orange juice and other citrus-based beverages, we carried out a double-blind clinical trial. Twelve healthy volunteers drank four citrus beverages on four distinct occasions: 1) freshly squeezed orange juice (FOJ), 2) commercially pasteurized 100% orange juice (POJ), 3) sugary drink with 30% orange juice (30% OJ), and 4) citrus-flavored sugary drink (citrus drink). Each beverage (500 mL) was consumed within 10 minutes time, and blood antioxidant activity was assessed before and five hours after intake. Total phenolic compounds, ascorbic acid and antioxidant capacity of the beverages were analyzed. The POJ exhibited the highest content of ascorbic acid and phenolic compounds, followed by FOJ and 30% OJ, while citrus drink had the lowest amount of these compounds (phenolic compounds was significantly different from FOJ and POJ; ascorbic acid was significantly different from all). Citrus drink also exhibited the lowest antioxidant capacity, while the other juices were not different from each other (P < 0.05). Although POJ, FOJ, and 30% OJ exhibited higher amounts of ascorbic acid and phenolic compounds, their intake did not result in increased blood antioxidant activity of these healthy individuals. However, neither were they associated with a decrease in blood antioxidant activity, as was observed after ingestion of citrus drink.
Keywords: fruit juice; sugary drinks; vitamin C; polyphenols; antioxidants